"Inherently Concerted" Topics. Issue 8 (August 2015) - Unknown
<x xml:space="preserve">Abstract</x> LaDonna George, a route driver who serviced vending machines, took off early from work one Friday without servicing her route or informing her boss, in violation of company policy. That weekend, George saw a "help wanted" ad for a vending machine company route driver. Her conscience must have been bothering her, because she immediately concluded that her employer was on to her and was advertising for her replacement.